HIV Aspartic Peptidase Inhibitors Modulate Surface Molecules and Enzyme Activities Involved with Physiopathological Events in Fonsecaea pedrosoi - Palmeira, Vanila F.; Alviano, Daniela S.; Braga-Silva, Lys A.; Goulart, Fátima R. V.; Granato, Marcela Q.; Rozental, Sonia; Alviano, Celuta S.; Santos, André L. S.; Kneipp, Lucimar F. (Frontiers in Microbiology, 2017)
Fonsecaea pedrosoi is the main etiological agent of chromoblastomycosis, a recalcitrant disease that is extremely difficult to treat. Therefore, new chemotherapeutics to combat this fungal infection are urgently needed. Although aspartic peptidase inhibitors (PIs) currently used in the treatment of human immunodeficiency virus (HIV) have shown anti-F. pedrosoi activity their exact mechanisms of action have not been elucidated. In the present study, we have investigated the effects of four HIV-PIs on crucial virulence attributes expressed by F. pedrosoi conidial cells, including surface molecules and secreted enzymes, both of which are directly involved in the disease development. In all the experiments, conidia were treated with indinavir, nelfinavir, ritonavir and saquinavir (100 μM) for 24 h, and then fungal cells were used to evaluate the effects of HIV-PIs on different virulence attributes expressed by F. pedrosoi. In comparison to untreated controls, exposure of F. pedrosoi cells to HIV-PIs caused (i) reduction on the conidial granularity; (ii) irreversible surface ultrastructural alterations, such as shedding of electron dense and amorphous material from the cell wall, undulations/invaginations of the plasma membrane with and withdrawal of this membrane from the cell wall; (iii) a decrease in both mannose-rich glycoconjugates and melanin molecules and an increase in glucosylceramides on the conidial surface; (iv) inhibition of ergosterol and lanosterol production; (v) reduction in the secretion of aspartic peptidase, esterase and phospholipase; (vi) significant reduction in the viability of non-pigmented conidia compared to pigmented ones. In summary, HIV-PIs are efficient drugs with an ability to block crucial biological processes of F. pedrosoi and can be seriously considered as potential compounds for the development of new chromoblastomycosis chemotherapeutics.